Reference charts for fetal biometric parameters in twin pregnancies according to chorionicity. (30th January 2014) - Araujo Júnior, Edward; Ruano, Rodrigo; Javadian, Pouya; Martins, Wellington P.; Elito Júnior, Julio; Pires, Claudio Rodrigues; Zanforlin Filho, Sebastião Marques
ABSTRACT Objective The objective of this article is to determine reference values for fetal biometric parameters in twin pregnancies and to compare these values between monochorionic and dichorionic pregnancies. Methods A retrospective cross‐sectional study was conducted among 157 monochorionic and 176 dichorionic twin pregnancies between 14 and 38 weeks of gestation. Biometric measurements included the biparietal diameter (BPD), abdominal circumference (AC), femurs length (FL) and estimated fetal weight (EFW). To evaluate the correlation between biometric parameters and gestational age, polynomial regression models were created, with adjustments using the coefficient of determination (R2). Comparison between monochorionic and dichorionic pregnancies was performed using analysis of covariance. Results The mean BPD, AC, FL and EFW for the dichorionic pregnancies were 56.16 mm, 191.1 mm, 41.08 mm and 816.1 g, respectively. The mean BPD, AC, FL and EFW for the monochorionic pregnancies were 57.14 mm, 184.2 mm, 39.29 mm and 723.4 g, respectively. There was a statistical difference between mono and dichorionic pregnancies for all the biometric parameters (BPD p = 0.012; AC p = 0.047; FL p = 0.007; EFW p = 0.011). Conclusion Reference curves of biometric parameters in twin pregnancies were determined. Biometric parameters were statistically different between monochorionic and dichorionic pregnancies. © 2014 John Wiley & Sons, Ltd.